Building capacities in Sub-Saharan African countries for antimicrobial resistance surveillance in the food and agriculture sectors using the FAO ATLASS tool - Ouoba, Labia Irene I.; Treilles, Michael; Noumedem, Ranyl Nguena Guefack; Keck, Nicolas; Kiptiness, Joshua Kimutai; Diallo, Alpha A.; Mouillé, Béatrice; Gourlaouen, Morgane; Kimani, Tabitha; Obonyo, Mark; Niang, Mamadou; Dsani, Esther; et al. (Frontiers in Veterinary Science, 2025)
FAO has developed the ‘Assessment Tool for Laboratories and AMR Surveillance Systems” (FAO-ATLASS) to support the national food and agriculture sectors in describing and assessing their AMR surveillance system in a standardized manner. Between 2018 and 2024, 221 laboratories and 24 national AMR surveillance systems were assessed in 27 Sub-Saharan African countries. The assessments assigned Progressive Improvement Pathway (PIP) stages from “1-limited” to “5-sustainable,” with stage “3-developed” considered sufficient for reliable AMR data production. The compilation of assessments enabled identification of common gaps that guided FAO interventions to efficiently support capacity building for AMR surveillance in Africa. The impact of the evaluations and follow-up interventions was investigated through a post-ATLASS survey involving 15 of the 27 countries assessed and 112 of the 221 laboratories. The assessments showed that 21 (9.5%) and 6 (2.7%) laboratories were at PIP stages 3 and 4, respectively, while other laboratories (86.5%) are at PIP stage 1 and 2. Two (8.3%) AMR surveillance systems were at PIP stage 3, and others (92.6%) were at PIP stage 1 or 2. Quality assurance was the most critical gap for laboratories; the access to reference strains, reagents, and participation to proficiency testing (PT) scheme were among the major common concerns. For surveillance systems, the data production (laboratory network and data collection/analysis) were the main areas to improve. The post-ATLASS survey carried out in 2024 indicated that over 90% of the countries and 50% of laboratories received support from FAO and partners mainly for training, provision of reagents and equipment (60%), enrolment in PT program (73%), development of AMR surveillance strategy and SOPs on AMR detection (53%). Ten laboratories moved from PIP stage 2 to 3, eight from stage 1 to 2, and two from stage 2 to 4. For about 60% of the laboratories, the respondents reported that the management showed better commitment in supporting AMR activities. Implementation of AMR surveillance is now effective in 80% of the countries surveyed (initial of 33%). The results of this analysis indicate that AMR surveillance systems are progressively improving in African countries; however, sustained efforts are necessary to ensure the production of reliable data in the majority of countries and to inform evidence-based interventions against AMR.